Association of serum 25-hydroxyvitamin D concentrations with sleep phenotypes in a German community sample - Dogan-Sander, Ezgi; Willenberg, Anja; Batmaz, İnci; Enzenbach, Cornelia; Wirkner, Kerstin; Kohls, Elisabeth; Mergl, Roland; Thiery, Joachim; Kratzsch, Jürgen; Hegerl, Ulrich; Sander, Christian (PloS one, 2019)
Sleep disorders and vitamin D deficiency are among the most common health problems. Few studies investigated the effect of vitamin D on objectively recorded sleep with sound methodological quality and reasonable temporal proximity. To investigate the relationship between serum 25-hydroxyvitamin D (25(OH)D) concentrations and objective sleep parameters assessed within close temporal proximity in a population-based sample. It is expected that higher serum 25(OH)D concentrations are associated with 1) better objective sleep outcomes (longer sleep duration, higher sleep efficiency, earlier mid-sleep time) and 2) more positive subjective sleep evaluations. A subset of participants (n = 1045) from the LIFE-Adult-Study was analysed. Measurement of serum 25(OH)D vitamin was performed using an electrochemiluminescence immunoassay. Actigraphic assessments were performed using SenseWear Pro 3 devices. The following objective sleep parameters were calculated: total sleep duration, night sleep duration, night sleep efficiency, midsleep time and wake after sleep onset (WASO). Subjective sleep evaluations were assessed via questionnaire (sleep quality (PSQI), daytime sleepiness (ESS)). Data were analysed applying a multiple linear regression model with a stepwise approach. The regression models revealed significant associations of serum 25(OH)D concentration with night sleep duration and midsleep time. No association was found for total sleep duration and night sleep efficiency. Higher serum 25(OH)D concentration was further associated with shorter WASO in males but longer WASO in females. Moreover, serum 25(OH)D concentration did not show any significant association with subjective sleep quality and daytime sleepiness. The results indicate that a higher concentration of serum 25(OH)D is associated with longer and earlier night sleep. Although the present study was able to demonstrate an association between serum 25(OH)D concentration and objective sleep parameters, no conclusion about underlying mechanisms or causal inferences can be drawn.